Pengaruh Kurikulum Merdeka terhadap Perkembangan Moral Anak Sekolah Dasar (SD) - Ariswan, Ariswan; Neviyarni, Neviyarni; Zen, Zulhendri (TSAQOFAH, 2025)
This article aims to examine the impact of the implementation of the Kurikulum Merdeka on the moral development of elementary school (SD) students through an approach that emphasizes flexibility, relevance, and student-centered learning. The study adopts a literature review method by analyzing the concepts of Kurikulum Merdeka, theories of moral development in elementary-aged children, and their potential interrelation in the learning context. The findings indicate that the flexibility offered by the Kurikulum Merdeka provides space for teachers to integrate moral values into instruction in a contextual manner aligned with students’ needs. Project-based and collaborative learning emphasized in the curriculum are considered effective in fostering empathy, responsibility, and social awareness from an early age. However, the effectiveness of implementation heavily depends on teachers’ understanding of children's moral development stages and their ability to design adaptive and meaningful instructional strategies. In conclusion, the Kurikulum Merdeka holds significant potential in supporting character formation and the moral development of elementary students, provided that its implementation is well-planned, contextual, and oriented toward the holistic developmental needs of children.